Extracorporeal Membrane Oxygenation for SARS-CoV-2 Acute Respiratory Distress Syndrome: A Retrospective Study From Hubei, China - Yang, Xiaobo; Hu, Ming; Yu, Yuan; Zhang, Xijing; Fang, Minghao; Lian, Yingtao; Peng, Yong; Wu, Lingling; Wu, Yongran; Yi, Jun; Zhang, Lu; Wang, Bing; et al. (Frontiers in Medicine, 2021)
Background The data on long-term outcomes of patients infected by SARS-CoV-2 and treated with extracorporeal membrane oxygenation (ECMO) in China are merely available. Methods A retrospective study included 73 patients infected by SARS-CoV-2 and treated with ECMO in 21 intensive care units in Hubei, China. Data on demographic information, clinical features, laboratory tests, ECMO durations, complications, and living status were collected. Results The 73 ECMO-treated patients had a median age of 62 (range 33 - 78) years and 42 (63.6%) were males. Before ECMO initiation, patients had severe respiratory failure on mechanical ventilation with a median PO2/FiO2 of 71.9 [interquartile range (IQR), 58.6 - 87.0] mmHg and a median PCO2 of 62 [IQR, 43 - 84] mmHg on arterial blood analyses. The median duration from symptom onset to invasive mechanical ventilation, and to ECMO initiation was19 [IQR, 15 - 25] days, and 23 [IQR, 19 - 31] days. Before and after ECMO initiation, the proportions of patients receiving prone position ventilation were 58.9% and 69.9%, respectively. The median duration of ECMO support was 18.5 [IQR 12 - 30] days. During the treatments with ECMO, major hemorrhages occurred in 31 (42.5%) patients, and oxygenators were replaced in 21 (28.8%) patients. Since ECMO initiation, the 30-day mortality and 60-day mortality were 63.0% and 80.8%, respectively. Conclusions In Hubei, China, the ECMO-treated patients infected by SARS-CoV-2 were of a broad age range and with severe hypoxemia. The durations of ECMO support, accompanied with increased complications, were relatively long. The long-term mortality in these patients was considerably high.